Photoelectron emission from lithiated diamond (Phys. Status Solidi A 10∕2014). Issue 10 (18th October 2014) - O'Donnell, Kane M.; Martin, Tomas L.; Edmonds, Mark T.; Tadich, Anton; Thomsen, Lars; Ristein, Jürgen; Pakes, Christopher I.; Fox, Neil A.; Ley, Lothar
Abstract : A lithium‐oxygen termination has been shown to induce negative electron affinity on diamond. O'Donnell and coworkers (pp.2209–2222 ) have carried out computational and experimental studies on such surfaces, focusing on the photoemission properties of lithiated diamond. Two methods of fabricating lithiated diamond are considered. A thick‐film process has the advantage of easy preparation but reproducibility remains problematic. A thin‐film process starting from oxygenterminated diamond is found to require a thermal activation after lithium deposition in order to induce negative electron affinity. Once activated, lithiated diamond remains stable after air‐exposure. Consequently there is hope that such surfaces will allow the realization of practical diamond‐based devices for electron emission.